Scientific basis of surveillance and control of hepatitis E in the temperate climate - A. V. Polyanina; T. N. Bystrova; E. I. Efimov (Журнал инфектологии, 2017)
Purpose of the study. Epidemiological characteristics of hepatitis E in the territory of the Central European region of Russia (on the example of the Nizhny Novgorod region) for the scientific justification of the system of epidemiological monitoring and surveillance of this infection.Materials and methods. Samples of blood sera from patients with a diagnosis of hepatitis (n=860); «сonditionally healthy» population, livestock keepers (n=3108); migrants from the republics of Central Asia (n=160). Twelve years of dynamic monitoring of the prevalence of antibodies to the hepatitis E virus among an adult «conditionally healthy» population (n=1359). To resolve the issue of the prescription period for infection, the avidity of IgG antibodies to the hepatitis E virus (n=37) was determined by an experimental series of the test system produced by «Diagnostic Systems». Serological markers of hepatitis E virus infection was determined by ELISA using commercial test kits. For the detection of HEV RNA in faeces samples of pigs analyzed by PCR using an experimental set of «Interlabservice».Results. Manifestations of the epidemic process the hepatitis E in Russia Central European region are characterized by: substantially higher than the conventional parameters, the intensity of the manifest (from 0,9±0,20 /0000 to 6,9±1,70 /0000), and the latent components (from (1,03±1,0% to 9,3±2,2%); a high proportion of the hepatitis E (from 8,3±2,3% to 13,0±2,9%) in the etiological structure of acute viral hepatitis; low manifestation; active involvement of the epidemic process in persons aged 30-49 years, workers of livestock farms (from 6,4±1,3% to 31,1±0,4%) and enterprises in the meat industry (from 9,1±3,8% to 19,1±2,9%) and migrants from regions with high activity of epidemic process (31,9±3,7%). Workers of cattle-breeding complexes and the enterprises of meat processing industry in areas of temperate climate are at high risk of hepatitis E infection. A significant prevalence of hepatitis E in the human population non-endemic regions may be due not only to importation of infection from endemic areas, but also by contact with animals and/or possible ingestion of insufficiently cooked meat that in the conditions of sporadic morbidity is indicative of mainly zoonotic nature of hepatitis E in the framework of realization of fecal-oral mechanism of transmission.Conclusion. The conducted research allowed to characterize the epidemiological features of hepatitis E in the territory of the Central European region of Russia and served as the basis for developing a system of epidemiological supervision and control for this differentiated nosology.